Interferon‐inducible protein 10 (IP‐10) is associated with viremia of early HIV‐1 infection in Korean patients. Issue 5 (10th February 2015) - Lee, SoYong; Chung, Yoon‐Seok; Yoon, Cheol‐Hee; Shin, YoungHyun; Kim, SeungHyun; Choi, Byeong‐Sun; Kim, Sung Soon
<x xml:space="preserve">Abstract</x> Cytokines/chemokines play key roles in modulating disease progression in human immunodeficiency virus (HIV) infection. Although it is known that early HIV‐1 infection is associated with increased production of proinflammatory cytokines, the relationship between cytokine levels and HIV‐1 pathogenesis is not clear. The concentrations of 18 cytokines/chemokines in 30 HIV‐1 negative and 208 HIV‐1 positive plasma samples from Korean patients were measured by the Luminex system. Early HIV‐1 infection was classified according to the Fiebig stage (FS) based on the characteristics of the patients infected with HIV‐1. Concentrations of interleukin‐12 (IL‐12), interferon‐inducible protein‐10 (IP‐10), macrophage inflammatory protein‐1α (MIP‐1α) and regulated upon activation, normal T cells expressed and secreted (RANTES) were increased significantly during the early stage of HIV‐1 infection (FS II–IV) compared with the HIV‐1‐negative group. Of these cytokines, an elevated level of IP‐10 was the only factor to be correlated positively with a higher viral load during the early stages of HIV‐1 infection (FS II–IV) in Koreans (R = 0.52, P < 0.0005). Therefore, these results suggest that IP‐10 may be an indicator for HIV‐1 viremia and associated closely with viral replication in patients with early HIV‐1 infection. J. Med. Virol. 87:782–789, 2015. © 2015 Wiley Periodicals, Inc.